2005
DOI: 10.1097/01.sap.0000151459.07978.fa
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Intervention and Capsular Contracture After Breast Augmentation

Abstract: Epidemiologic data on local complications after breast augmentation are scarce. In particular, few prospectively collected data are available on modern breast implants on this issue. Using data from the Danish Registry for Plastic Surgery of the Breast, the authors examined determinants of surgery-requiring complications and capsular contracture grades III to IV among 2277 women who underwent cosmetic breast implantation from June 1999 through April 2003. During an average follow-up period of 1.6 years after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
1
14

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(108 citation statements)
references
References 35 publications
(44 reference statements)
2
91
1
14
Order By: Relevance
“…Of note by the senior author, an excellent outcome for both procedures can be performed with not only no additional morbidity with the combined procedures, but also a marked reduction of capsular contracture graded higher than a Baker I, relative to traditional dual incision approaches [6][7][8][9][10]. The implications for capsular contracture in this study in general are, in the senior author's view, significant, given that the senior author's experience of several thousand breast augmentations in his career, have yielded the classic rate of capsular contracture between 5 and 10% [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Of note by the senior author, an excellent outcome for both procedures can be performed with not only no additional morbidity with the combined procedures, but also a marked reduction of capsular contracture graded higher than a Baker I, relative to traditional dual incision approaches [6][7][8][9][10]. The implications for capsular contracture in this study in general are, in the senior author's view, significant, given that the senior author's experience of several thousand breast augmentations in his career, have yielded the classic rate of capsular contracture between 5 and 10% [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiology of capsular contracture remains unclear, but previous studies have suggested that it is associated with chronic inflammatory factors, such as a foreign body reaction to the implant, the surface property of the implant, site of implant placement, postoperative bacterial infections, hematoma, or seroma [5,6]. Studies have examined whether inhibiting inflammatory events that cause a fibrosis is effective in preventing the capsular contracture, demonstrating that anti-inflammatory agents (e.g., calcium channel blockers), angiotensin-converting enzyme inhibitors, and leukotriene receptor antagonists (e.g., zafirlukast and montelukast) were effective in reducing the degree of capsular contracture [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Capsular contracture around breast implants is an unpredictable and common complication after breast augmentation and reconstruction with an overall prevalence of up to 17%. [7][8][9][10][11][12] Growing evidence suggests that capsular contracture is associated with subclinical infection of breast implants. The predominantly isolated microorganism from bacteriologic cultures of contracted capsules is Staphylococcus epidermidis.…”
Section: Introductionmentioning
confidence: 99%